2019
DOI: 10.1111/exsy.12428
|View full text |Cite
|
Sign up to set email alerts
|

Multiattribute decision making based on power operators for linguistic intuitionistic fuzzy set using set pair analysis

Abstract: The aim of the presented paper is to give a multiattribute decision making (MADM) method under the linguistic intuitionistic fuzzy (LIF) environment using the set pair analysis (SPA) theory. LIF set can express the qualitative information in terms of linguistic variables, whereas the connection number (CN) based on the “identity,” “discrepancy,” and “contrary” degrees of the SPA theory handles the uncertainties and certainties systems. On the basis of these features, we develop some series of linguistic CN (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Based on its advantages, it is concluded that the presented theory can model the uncertainties with more enhancements as compared to the primitive environments. In the future, we shall lengthen the application of the proposed measure to the diverse fuzzy environment such as Pythagorean set [54][55][56], linguistic environment [57][58][59], as well as different fields of application such as supply chain management, emerging decision problems, risk evaluation, etc. [60][61][62][63] .…”
Section: Resultsmentioning
confidence: 99%
“…Based on its advantages, it is concluded that the presented theory can model the uncertainties with more enhancements as compared to the primitive environments. In the future, we shall lengthen the application of the proposed measure to the diverse fuzzy environment such as Pythagorean set [54][55][56], linguistic environment [57][58][59], as well as different fields of application such as supply chain management, emerging decision problems, risk evaluation, etc. [60][61][62][63] .…”
Section: Resultsmentioning
confidence: 99%
“…HFSs developed with linguistic expressions allow decision makers to make their evaluations with a wide set of linguistic expressions. Thus, HFLTS provides an opportunity to be used in various scientific fields with different approaches [26,[28][29][30].…”
Section: Hesitant Fuzzy Sets and Linguistic Termsmentioning
confidence: 99%
“…Liu and You [30] continued to study AOs for LIFNs based on Einstein t-norm and t-conorm. Garg and Kumar [31] investigated novel LIF power AOs based on set pair analysis. These aforementioned MAGDM methods reveal the powerfulness and capability of LIFSs in dealing with practical MAGDM problems; however, LIFSs still have drawbacks when expressing DMs' evaluation values.…”
Section: Introductionmentioning
confidence: 99%